A prison mental health in‐reach model informed by assertive community treatment principles: evaluation of its impact on planning during the pre‐release period, community mental health service engagement and reoffending. (3rd November 2014) - McKenna, Brian; Skipworth, Jeremy; Tapsell, Rees; Madell, Dominic; Pillai, Krishna; Simpson, Alexander; Cavney, James; Rouse, Paul
Abstract: Background: It is well recognised that prisoners with serious mental illness (SMI) are at high risk of poor outcomes on return to the community. Early engagement with mental health services and other community agencies could provide the substrate for reducing risk. Aim: To evaluate the impact of implementing an assertive community treatment informed prison in‐reach model of care (PMOC) on post‐release engagement with community mental health services and on reoffending rates. Methods: One hundred and eighty prisoners with SMI released from four prisons in the year before implementation of the PMOC were compared with 170 such prisoners released the year after its implementation. Results: The assertive prison model of care was associated with more pre‐release contacts with community mental health services and contacts with some social care agencies in some prisons. There were significantly more post‐release community mental health service engagements after implementation of this model ( Z = −2.388, p = 0.02). There was a trend towards reduction in reoffending rates after release from some of the prisons ( Z = 1.82, p = 0.07). Conclusions and implications for practice: Assertive community treatment applied to prisoners with mental health problems was superior to 'treatment as usual', but more work is needed to ensure that agencies will engage prisoners in pre‐release care. The fact that the model showed some benefits in the absence of any increase in resources suggests that it may be the model per se that is effective. Copyright © 2014 John Wiley & Sons, Ltd.